Epistemologi Pragmatisme - Anastasia Jessica Adinda (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
The influence of Pragmatism that is so evident in various fields of life makes a review of Pragmatism’s epistemology important. This paper aims to recognize and review the boundaries of Pragmatism’s epistemology. The method used in this study is hermeneutics of the text. The main questions of this study are: “What is the Epistemology of Pragmatism?” And “What is the criticism of the epistemology of Pragmatism?” In order to answer this problem, it will be elaborated respectively: Basic Elements in Epistemology, Analysis of Principles Epistemology in Pragmatism and Critical Evaluation of the Epistemology of Pragmatism.